Poster 254: Improvements in Kujala at Minimum Two-Years Following Medial Patellofemoral Ligament Reconstruction are Correlated with Intraoperative Instability Measurements: A Multivariate Analysis of Risk Factors - Yanke, Adam B.; Elias, Tristan J.; Haneberg, Erik; Phillips, Andrew R.; Kaplan, Daniel J.; Sachdev, Divesh; Wang, Zachary; Credille, Kevin T.; Chahla, Jorge; Forsythe, Brian; Verma, Nikhil N.; Cole, Brian J. (Orthopaedic journal of sports medicine, 2024)
Objectives: Isolated medial patellofemoral ligament reconstruction (MPFLR) is an effective treatment for those suffering from patellofemoral instability. Currently, many concomitant procedures are associated with MPFLR that address underlying pathologic anatomy. The indication and need for such procedures are currently not well understood and often involve the use of more invasive techniques. We aim to identify patients who may be more vulnerable to worse outcomes. The purpose of this study is to correlate demographic, anatomical, and clinical risk factors to minimum two-year outcomes following isolated MPFLR. Methods: A retrospective review of patients undergoing isolated MPFLR for recurrent patellar instability at a single institution between December 2015-June 2021 was performed. Patients with concomitant osseous procedures beyond chondroplasty and any ligamentous procedure were excluded. Included patients completed patient reported outcome (PRO) surveys preoperatively then at a minimum of 2 years postoperatively. Demographic, radiographic, surgical, and clinical data was collected. Univariate correlations to minimum 2-year delta-PRO scores were calculated, then those reaching significance were included in a multivariable linear regression analysis. Results: One hundred and thirteen MPFLR patients were included (77 female, 36 male; age: 21.6 ± 9.1 years). Final Kujala score was 88.44 ± 14.12 at 2.97 ± 1.11 years postoperatively. On univariate testing, final Kujala score was significantly correlated with age at time of surgery (P=0.035; r=0.218), body mass index (P=0.035; r=-0.204), and the degree of knee flexion at which the patella can no longer be manually dislocated laterally during an examination under anesthesia (Instability Resolution Angle — IRA; P=0.010; r=-0.318). The delta final Kujala score (mean score 30.72 ± 19.68) was significantly correlated with age at time of surgery (P=0.032; r=-0.207), age at time of first patellar instability event (P=0.001; r=0.364), Caton-Deschamps Index (CDI; P=0.026; r=-0.235), trochlear width (P=0.016; r=0.251), the percentage of trochlear-patellar overlap on sagittal MRI (P=0.031; r=0.227), and the depth of the central trochlear trough from the lateral trochlear peak (P=0.035; r=0.221)( Table 1 ). On multivariable linear regression analysis, a larger IRA remained significantly correlated with worse final Kujala scores (P= 0.018) and delta final Kujala (P= 0.04). Conclusions: A larger IRA on examination under anesthesia is independently correlated with worse final and delta final Kujala scores at a minimum of two-years after isolated MPFLR. This finding can help guide surgeons in their decision to do an isolated MPFLR or add in larger, more invasive procedures that address underlying anatomic pathologies.